Initial prognoctic factors of traumatic brain injury, complicate by acute, traumatic subdural hematoma and epidural hematoma and their association with outcome - Bartłomiej Kulesza; Paweł Szmygin; Adam Nogalski (Kazimierz Wielki University, 2017)
Traumatic brain injury (TBI) is not just one disease, but includes a wide spectrum alteration in brain function, or other evidence of brain pathology caused by external force.  The most important effect of traumatic brain injury is the development of the intracranial haematomas. It is estimated thet intracranial hematomas occur In 25-45% of severy traumatic brain injuries, 3-12% of moderate cases, and 0,2% of mild craniocerebral injuries.  The mostly consequence of injury is acute subdural hematoma or epidural hematoma. Initial prognostic factors could be divided In:  demographic factors, vital signs, laboratory parameters and Computer Tomography scan characteristics. Demographic factors as: age, gender,  Glasgow coma scale, mechanism of injury, time injury-surgery. Vital signs: blood pressure, saturation, heart and respiratory rate, among that factors there are secondary brain injury so hypotensia and hipoxia. Laboratory paremeters include routine laboratory test were taken measuremets. Computer Tomography scan characteristics include Marshall and Roterdam scale and independent characterics. A lot of that factors has been requiring research yet. Particulary factors from vital sings and laboratory paremeters In patients with acute, traumatic subdural hematoma and epidural hematoma.